Agronomic viability of New Zealand spinach and kale intercropping - Cecilio Filho, Arthur B. [UNESP]; Bianco, Matheus S. [UNESP]; Tardivo, Caroline F. [UNESP]; Pugina, Gabriel C. M. [UNESP] (Acad Brasileira De Ciencias, 2017)
The intercropping is a production system that aims to provide increased yield with less environmental impact, due to greater efficiency in the use of natural resources and inputs involved in the production process. An experiment was carried out to evaluate the agronomic viability of kale and New Zealand spinach intercropping as a function of the spinach transplanting time. (0, 14, 28, 42, 56, 70, 84 and 98 days after transplanting of the kale). The total yield (TY) and yield per harvest (YH) of the kale in intercropping did not differ from those obtained in monoculture. The spinach TY was influenced by the transplanting time, the earlier the transplanting, the higher the TY. The spinach YH was not influenced by the transplanting time, but rather by the cultivation system. In intercropping, the spinach YH was 13.5% lower than in monoculture. The intercropping was agronomically feasible, since the land use efficiency index, which was not influenced by the transplanting time, had an average value of 1.71, indicating that the intercropping produced 71% more kale and spinach than the same area in monoculture. Competitiveness coefficient, aggressiveness and yield loss values showed that kale is the dominating species and spinach is the dominated.
Keywords: Tetragonia expansa; Brassica oleracea var. acephala; cultivation system; land use efficiency; competition index